Benefits of exercise in pregnancies with gestational diabetes. (3rd July 2022) - Halvatsiotis, Panagiotis; Panagiotou, Ourania; Koulouvaris, Panagiotis; Raptis, Athanasios; Bamias, Aristotelis; Kalantaridou, Sophia; Valsamakis, Georgios
Abstract: A significant proportion of pregnancies are complicated by diabetes mellitus. Most of them concern women with gestational diabetes mellitus, while proportionally are presented with preexisting DM 1 and DM 2. Metabolic derangements of the diabetic syndrome are likely to generate serious complications for both the mother and the fetus with a significant impact on their later health. Undoubtedly, all appropriate interventions that will contribute to the smoothest and most uncomplicated course of pregnancy are considered essential. Healthy diet adjustments, glucose monitoring and an appropriate insulin regimen, if needed, are considered effective tools for a safe gestation. Courses with aerobic, anaerobic stretching and relaxation exercises are presented with significant benefits in the therapeutic struggle for the general public. Extended research has been conducted assessing the role of exercise incorporation in a diabetic pregnancy. As evidence would support based on recent literature, exercise is an important mean in the prevention of carbohydrate intolerance during gestation and even more facilitates a smoother management of a diabetic pregnancy. Thus, exercise poses an essential role for maternal and neonatal health.